Science Learning Transformation: Android Digital Comics (MiGiRo) as a Science Learning Resource on the Concept of Genetics - Diniya, Diniya; Amaliyah, Fitri; Syarif, Muhammad Ilham; Oshima, Ryugo; Abe, Yoichiro (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The learning resources used by teachers in science education, such as textbooks and student worksheets, are often less engaging and primarily limited to occasional presentations. Students grow disinterested and distracted as a result of this lack of variation. This study set out to assess the efficacy, usefulness, and reactions of junior high school students to the employment of Android-based digital comics (MiGiRo) as a teaching tool for the subject of genetics. The Research and Development (R&D) method with the Plomp model was employed. Validation was conducted by material experts, media experts, and linguists, while practicality was assessed by science teachers, and student responses were collected from ninth-grade students. The data were analyzed quantitatively. The validation results indicated that MiGiRo received scores of 86.3% from material experts, 75% from media experts, and 92.5% from linguists, all within the very good category, making it suitable for use. The practicality test showed a score of 96.7%, indicating that MiGiRo is very practical with no revisions needed. Student response testing during the field trial resulted in an overall score of 88.3%, also in the very good category. It can be concluded that MiGiRo is a useful and legitimate interactive learning tool for junior high school students.